Omic tools to study enzyme production from fungi in the Pleurotus genus - Maura Téllez-Téllez; Gerardo Díaz-Godínez (BioResources)
Fungi from the Pleurotus genus secrete different enzymes, including laccases, manganese peroxidases, versatile peroxidases, glycosyl hydrolases, peptidases, and esterases/lipases. This genus contains white-rot fungi, which degrade the components of plant materials. The secreted enzymes have great application in the biotechnology field. The general conditions of a fungal culture have a direct effect on the regulation of protein expression, which changes the composition of the transcriptome, proteome, and secretome. Studies have shown that the culture type, either solid or submerged, also changes the transcriptional profiles. The knowledge of the transcriptome and proteome allows one to find valuable enzymes to obtain portable fuels from lignocellulosic materials and provide information oriented to improve the enzymes production through different culture conditions. Additionally, research has been conducted on the Pleurotus genus to better understand its biology. Numerous tools have been used for this purpose, such as classical recombination, genetic engineering, and omic tools. The information generated by the omic sciences (comparative genomics, transcriptomics, proteomics, and metabolomics) and through bioinformatics (massive data analysis), among other things, can greatly contribute to improving production processes and the use of metabolites. This review discussed some works where omic tools have been used to study enzyme production of fungi of the Pleurotus genus.